2008
DOI: 10.1080/13668250802282944
|View full text |Cite
|
Sign up to set email alerts
|

The effect of active support training on engagement, opportunities for choice, challenging behaviour and support needs

Abstract: The results contribute to a growing body of evidence demonstrating favourable outcomes of AS in terms of engagement and challenging behaviour in people with ID. Surprising results are presented for choice and perceived support needs, warranting further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(78 citation statements)
references
References 11 publications
2
70
0
6
Order By: Relevance
“…Three focused on issues to do with communication of information, and found that supporting people to make decisions involves listening to them (Hoole and Morgan, 2011), asking about their preferences and choices in an open and non-challenging way (Antaki, Finlay, Walton & Pate, 2008), and providing clear and simple written information (Wong, Clare, Holland, Watson & Gunn, 2000). The next three studies reported beneficial effects of support training (Koritsas, Iacono, Hamilton & Leighton, 2008;Robertson et al, 2005) and end of life decision support tools for staff (Karp 2009) on patient choice and the quality of support offered. The final two studies in this theme (Foy, MacRae, Thom & Macharouthu, 2007;Hossler, Levi, Simmons & Green, 2011) explored the use of different media to improve implementation.…”
Section: Improving the Implementation Of Supported Decision Makingmentioning
confidence: 99%
See 1 more Smart Citation
“…Three focused on issues to do with communication of information, and found that supporting people to make decisions involves listening to them (Hoole and Morgan, 2011), asking about their preferences and choices in an open and non-challenging way (Antaki, Finlay, Walton & Pate, 2008), and providing clear and simple written information (Wong, Clare, Holland, Watson & Gunn, 2000). The next three studies reported beneficial effects of support training (Koritsas, Iacono, Hamilton & Leighton, 2008;Robertson et al, 2005) and end of life decision support tools for staff (Karp 2009) on patient choice and the quality of support offered. The final two studies in this theme (Foy, MacRae, Thom & Macharouthu, 2007;Hossler, Levi, Simmons & Green, 2011) explored the use of different media to improve implementation.…”
Section: Improving the Implementation Of Supported Decision Makingmentioning
confidence: 99%
“…In Victoria, Australia, Koritsas et al (2008) conducted a before-and-after study to evaluate the impact of active support training delivered to support workers of people with intellectual disabilities. Active support was designed to enhance the interactions between support workers and people with disabilities in a structured manner, through the use of domestic activities.…”
mentioning
confidence: 99%
“…The implementation of active support in community residences for people with developmental disabilities has increased over the past decade (Jones et al, 1999;Koritsas, Iacono, Hamilton, & Leighton, 2008;Stancliffe, Harman, Toogood, & McVilly, 2008;Toogood, 2008). Many investigators have attempted to establish the efficacy of active support, but with varied results Bradshaw et al, 2004;Jones et al, 1999;Jones, Felce, Lowe, Bowley, Pagler, & Gallagher, 2001;Jones, Felce, Lowe, Bowley, Pagler, Strong, et al, 2001;Mansell, Beadle-Brown, Whelton, Beckett, & Hutchison, 2008;Mansell, Elliott, BeadleBrown, Ashman, & MacDonald, 2002;Mansell, McGill, & Emerson, 2001;Stancliffe, Harman, Toogood, & McVilly, 2007;Toogood, 2008); however, some researchers have argued that its efficacy is well-proven and future studies should instead be focused on refining its effects and applying it more widely (Stancliffe, Jones, & Mansell, 2008).…”
mentioning
confidence: 99%
“…Ockenden, Ashman, and Beadle-Brown have drawn on comprehensive and growing research into the benefits of active support, which has been conducted by various research groups situated largely in the United Kingdom (Jones et al, 2001;Mansell, BeadleBrown, Whelton, Beckett, & Hutchinson, 2008;Totsika, Toogood, Hastings, & Nash, 2008) and Australia (Koritsas, Iacono, Hamilton, & Leighton, 2008;Mansell, BeadleBrown, & Bigby, 2013;Stancliffe, Harman, Toogood, & McVilly, 2007. This expanded research base has enabled deeper exploration of the relationship between engagement in meaningful relationships and activities, and the provision of active support.…”
Section: Commentarymentioning
confidence: 95%